Ibero American Heritage in Mathematics and Mathematics Education. An overview from 40 notes - Rico, Luis (Historia y Memoria de la Educación, 2019)
This document presents a selection of data and events that have taken place in Ibero American countries on mathematics and mathematics education. Using a diachronic approach, we describe the presence and diffusion of mathematical and educational knowledge in the history of science from the fifteenth century to the present day, exemplified by a selection of ideas, knowledge and thought expressed and disseminated in Spanish. The work has been carried out with the collaboration of a large group of professors and researchers in mathematics and mathematics education from different Ibero American countries and communities. The Ibero-American heritage shown here underlines a historical constant of these countries, exemplified by its scientific development over the course of time. The action of its protagonists is presented in a comprehensive and structured historical framework, which helps to interpret, identify and describe the scientific and educational activity that that has taken place. This includes studies and academic production; materials that have been elaborated; the editing and circulation of scientific journals; congresses and symposiums that have been held; commissions that have been constituted; and the publication of books and other texts. The true protagonists of this activity are the groups, societies and experts, together with the institutions that are helping to form future teachers, mathematicians and researchers. The work Ibero American Heritage in Mathematics and Mathematics Education tells the story of the development and dissemination of these disciplines in the Ibero-American community with the contribution of institutions, societies, groups, communities and individuals.